Achievement inequalities in Hamburg schools: How do they change as students get older? - Caro, D; Lehmann, R (2009)
A handful of studies have found evidence of a gap in academic achievement between students of high- and low-socioeconomic status (SES) families. Furthermore, some scholars argue that the gap tends to widen as students get older. Evidence is, however, inconclusive and relies mostly on limited methodological designs. Drawing on the Hamburg School Achievement Census 1996 to 2000 (LAU 5, 7, and 9), the authors examined the trajectory of the math and reading achievement gap associated with SES from the age of 10 to 15 years by means of cross-random-effects, panel data, and hierarchical linear models (HLM). The use of 3 time points and statistical techniques well suited to the longitudinal data contribute to the methodological advance of measurement of the gap trend. The findings indicate a narrowing gap over the course of secondary school years and are interpreted in light of the relatively open and egalitarian school policies in Hamburg.